The Density Functional Theory (DFT) And DFT+U Study of the Effect of the on-Site Coulomb Repulsion Parameter U on the Structural and Magnetic Properties of CeO2 Nanoparticles - Kabir, Alamgir; Nishat, Sadiq Shahriyar; Rahman, Sumaya (Bangladesh Journal of Physics, 2020)
a